2019
DOI: 10.1093/brain/awz054
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction models in AQP4-IgG positive neuromyelitis optica spectrum disorders

Abstract: Using an international data set of 441 patients with AQP4-IgG positive NMOSD, and a collective history of almost 2000 attacks, Palace et al. apply mathematical modelling to predict likelihood of relapse and disability at different time points. Such estimates will help clinicians when counselling patients and aid drug trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 38 publications
11
156
2
6
Order By: Relevance
“…The implications of this report are limited by the fact that this is a single case. Although we did not find any other cases in the literature of mirror-image lesions reported in association with AQP4 positive NMOSD, a recent international study supported the tendency of sequential NMO relapses to have similar localizing features (13). One reason why we may be the first to report this phenomenon is that it is difficult to discern mirror-image lesions in NMOSD in locations other than the brain.…”
Section: Discussioncontrasting
confidence: 63%
“…The implications of this report are limited by the fact that this is a single case. Although we did not find any other cases in the literature of mirror-image lesions reported in association with AQP4 positive NMOSD, a recent international study supported the tendency of sequential NMO relapses to have similar localizing features (13). One reason why we may be the first to report this phenomenon is that it is difficult to discern mirror-image lesions in NMOSD in locations other than the brain.…”
Section: Discussioncontrasting
confidence: 63%
“…A recent report also evaluated the usefulness of previous attacks for predicting the future clinical course. 12 Although the report did not conclude on the importance of selecting patients with a recent high disease activity for clinical trials, the data suggested that the relapse rate in the following 2 years may be affected by the number of attacks in the past 2 years. Considered together with the results of this study that the relapse rates are significantly different between during the "clustered" and "nonclustered" intermittent periods, allocating the patients without taking the present disease activity into consideration in clinical trials may cause biases in the achieved results.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Neuromyelitis optica (including AQP4-IgG-positive) is an inflammatory disorder that is characterized by recurrent episodes of optic neuritis. While the involvement of specific cell types in activating these episodes remains unknown, the variability of the clinical manifestations according to the racial group, age of onset, the number of episodes (Palace et al 2019) reflect phenotype diversity that might be governed by an individual ASE-V genomic makeup. Moreover, a recent GWAS that tested the intensity and pattern of mosquito bite revealed predisposition of alleles that are in association with T-cell regulation (Jones et al 2017).…”
Section: Ase Genes Signify a Risk For A Broad Spectrum Of Immunologicmentioning
confidence: 99%